2011
DOI: 10.1002/chem.201002754
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach for the Characterization of Mucin‐Type Glycopeptides: The Effect of O‐Glycosylation on the Conformation of Synthetic Mucin Peptides

Abstract: Despite the growing importance of mucin core O-glycosylation in many biological processes including the protection of epithelial cell surfaces, the immune response, cell adhesion, inflammation, and tumorigenesis/metastasis, the regulation mechanism and conformational significance of the multiple introduction of α-GalNAc residues by UDP-GalNAc:polypeptide N-acetylgalactosaminyltransferases (ppGalNAcTs) remains unclear. Here we report an efficient approach by combining MS and NMR spectroscopy that allows for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 101 publications
2
35
0
Order By: Relevance
“…O-glycosylation has been shown to induce various protein conformational changes. Serine, threonine O-glycosylation with α -D-GalNAc for example, was reported to decrease the α -helical content of the modified peptide hormone calcitonin (Tagashira et al 2002), or even elicit β -like, extended structures in glycopeptides, which, in turn, were detected by large, residue-specific chemical shift changes (Coltart et al 2002; Hashimoto et al 2011). In contrast, it has been observed that O-glycosylation with β -D-glucose increases α -helicity (Corzana et al 2006a), while O-glycosylation with β -D-GlcNAc was reported to induce turn-like structures in several glycopeptides (Simanek et al 1998; Wu et al 1999).…”
Section: Glycosylationmentioning
confidence: 99%
“…O-glycosylation has been shown to induce various protein conformational changes. Serine, threonine O-glycosylation with α -D-GalNAc for example, was reported to decrease the α -helical content of the modified peptide hormone calcitonin (Tagashira et al 2002), or even elicit β -like, extended structures in glycopeptides, which, in turn, were detected by large, residue-specific chemical shift changes (Coltart et al 2002; Hashimoto et al 2011). In contrast, it has been observed that O-glycosylation with β -D-glucose increases α -helicity (Corzana et al 2006a), while O-glycosylation with β -D-GlcNAc was reported to induce turn-like structures in several glycopeptides (Simanek et al 1998; Wu et al 1999).…”
Section: Glycosylationmentioning
confidence: 99%
“…However, little is known about the mechanism of electron capture for glycopeptides, and thus more intensive ECD experiments are required using glycopeptides with different amino acid sequences, glycosylation sites, and/or glycan moieties to understand the ECD mechanism in an electron energy-dependent manner. 36 Since it is difficult to predict the electron energy for the highest ion score only from the precursor ion's m/z, we conclude that the ECD spectra should generally be obtained at various electron energies.…”
Section: Resultsmentioning
confidence: 82%
“…Besides MUC5AC glycopeptides, we have also analyzed various mucin-like glycopeptides using ECD at different electron energies, and contributed to the structural and functional elucidation of complicated glycopeptides. [34][35][36] In summary, we have demonstrated the effectiveness of our technique for the unambiguous identification of glycopeptides with specific glycans by the experiments using synthetic glycopeptides. Firstly, ECD spectra for each glycopeptide were obtained at different electron energies; e.g., 1, 6, and 9 eV.…”
Section: Muc5ac-7 At 9 Evmentioning
confidence: 76%
See 1 more Smart Citation
“…no: P15941), which is anchored to the apical surface of many epithelia, is of significant interest, not only from an analytical standpoint, but also because of its involvement in many biological processes [17]. Recently, the specific glycosylation at a single Thr residue in MUC-4 was shown to stabilise the protein backbone structure [18]. It is well known that the O-glycosylation of MUC-1, which is found predominantly in the extracellular VNTR region, undergoes pathology-dependent alterations.…”
Section: Introductionmentioning
confidence: 99%